First record of the deep-sea anglerfish Ceratias uranoscopus Murray, 1877 (Lophiiformes, Ceratiidae) from the Tropical Eastern Pacific Ocean - Rojas Rodríguez, Pablo (2024)
In 1973, a specimen of the deep‑sea anglerfish Ceratias uranoscopus Murray, 1877 was collected at a depth of 1000 m off the Pacific coast of Panama. This specimen represents (1) the first verified occurrence record of this species and genus in the Tropical Eastern Pacific Ocean and (2) an extension of about 7000 km east on this species’ previously known distribution. In this contribution, we provide and discuss unpublished and comparative morphometric, meristic, and occurrence data, corroborating the identity of the specimen and species and validating the new geographic range.